IDENTIFYING RISK FACTORS FOR THE SPREAD OF DRUG-RESISTANT TUBERCULOSIS IN LAMPUNG IN 2023: A CASE-CONTROL STUDY: Analisis Faktor Risiko Penyebaran Tuberkulosis Resisten Obat di Provinsi Lampung Tahun 2023 - Awaliyah, Kharismatul; Farich, Achmad; Muhani, Nova; Amirus, Khoidar; Eka Sari Siregar, Fitri (Jurnal Berkala Epidemiologi, 2025)
Background: Drug-resistant tuberculosis (DR-TB) is a growing health concern in Lampung, where the low rate of DR-TB case detection and high treatment failure rates emphasize the necessity of identifying risk factors to strengthen control measures for DR-TB. Purpose: This study aimed to identify the dominant risk factors for the spread of drug-resistant tuberculosis among patients in Lampung Province in 2023. Methods: Using a case-control study design, the research utilized secondary data from the Tuberculosis Information System (SITB) Lampung Province. A total sampling method was employed, with 126 respondents in the case group and a 1:1 ratio, making the total sample size 252 respondents. Data matching was done for gender and age variables. Statistical analysis included univariate, bivariate chi-square, and multivariate logistic regression tests. Results: Univariate analysis showed that 57.90% of respondents were male, 57.90% were in the at-risk age group, 58.30% were employed, 81.30% did not have diabetes (DM) comorbidity, 97,20% did not have HIV comorbidity, 67,50% had no prior TB treatment history. Bivariate analysis indicated significant associations with occupation (p-value 0.04), DM comorbidity (p-value 0.02), and treatment history (p-value 0.00). Gender, age, and HIV comorbidity showed no significant associations. The multivariate analysis showed a significant effect of the TB treatment history variable (p-value 0.00, OR=9.04) and the HIV comorbidity variable (p-value 0.03, OR= 0.08). Conclusion: TB treatment history is the dominant factor that can affect the spread of drug-resistant tuberculosis in Lampung Province in 2023. Future researchers are encouraged to focus on studying the types of treatment failures.